Impact of Alternative Skin Contact Procedures on the Aroma Composition of White Wine - Bavčar, D.; BaÅ¡a ÄŒesnik, H.; ÄŒuÅ¡, F.; Vanzo, A.; GaÅ¡perlin, L.; KoÅ¡merl, T. (South African Journal of Enology and Viticulture, 2011)
Zelen, Ribolla Gialla and Malvasia Istriana, grapes from the Vitis vinifera (L.) varieties, were subjected to four processes involving grape skin contact. Fresh and fruity young wines were produced by adding 6% or 12% grape berries, respectively, during alcoholic fermentation, freezing the pomace (Fp) and the freezing whole grapes (Fg). Wine-free volatile aromatic compounds were determined using two extraction techniques coupled to gas chromatography (GC). These aromatic compounds and wine standard chemical parameters were compared to control wines produced without skin contact. Esters, higher alcohols, terpenes, volatile phenols and C6 alcohols proved to be the most important sensorial odorants in wines. Both the content of aromatic compounds and the odour activity values showed some positive effects from skin contact. The freezing of the grapes and addition of 12% grape berries proved most effective for Zelen and Malvasia Istriana, producing a more intensive fruity and floral odour, a less intensive solvent odour and additional freshness. The same processes resulted only in additional fruitiness or a less intensive solvent odour in Ribolla Gialla while the lowest concentrations of grape derived terpenes were achieved for this variety. The three varieties were most affected by freezing processes. During the sensorial evaluation, the wines that had been subjected to skin contact were generally preferred to the control wines.